Childhood Intra-Thoracic Tuberculosis Clinical Presentation Determines Yield of Laboratory Diagnostic Assays - Singh, Urvashi B.; Verma, Yogita; Jain, Rakhi; Mukherjee, Aparna; Gautam, Hitender; Lodha, Rakesh; Kabra, Sushil K. (Frontiers in Pediatrics, 2021)
Background: Diagnosis of Intra-thoracic Tuberculosis (ITTB) in children is difficult due to pauci-bacillary nature of disease, challenge in collecting appropriate specimens, low sensitivity of smear microscopy and culture. Culture and Xpert MTB/RIF provide higher diagnostic yield in adults than in children. Objectives: Current study was designed to understand poor yield of diagnostic assays in children. Methods: Children with presumptive ITTB were subjected to gastric aspirates and induced-sputum twice. Samples were tested by Ziehl-Neelsen stain, Xpert MTB/RIF-assay and MGIT-960 culture. Subjects were grouped as Confirmed, Unconfirmed and Unlikely TB, and classified as progressive primary disease (PPD, lung parenchymal lesion) and primary pulmonary complex (PPC, hilar-lymphadenopathy) on Chest X-ray. Results: Of children with Confirmed TB 51/394 (12.9%), Unconfirmed TB 305 (77.4%) and Unlikely TB 38 (9.6%), 9(2.3%) were smear positive, 95(24.1%) Xpert-MTB/RIF positive and 51(12.9%) culture positive. Xpert-MTB/RIF detected 40/51 culture confirmed cases (sensitivity 78.4% and NPV 96.3%). Culture was positive in more children presenting as PPD (p<0.04). Xpert-MTB/RIF was positive in 78% of children with Confirmed TB. In unconfirmed TB group, Xpert positivity was seen in 31% of those with PPD and 11.9% in those with PPC (p<0.001). Conclusion: Xpert-MTB/RIF improved diagnosis by two-fold and increased detection of MDR-TB. Both liquid culture and Xpert-MTB/RIF gave higher yield in children with lung parenchymal lesions. Children with hilar lymphadenopathy without active lung parenchymal lesions, had poor diagnostic yield even with sensitive nucleic acid amplification tests, due to paucibacillary/localized disease, suggesting possible utility of invasively collected samples in early diagnosis and treatment.